Ottoman Approach to Shia and Sunni State Officers of Syria in the Examples of Fakhreddin Maanoğlu and Ali Canpolad between 1570s and 1630s - Birol Gündoğdu (Cumhuriyet İlahiyat Dergisi)

(untitled)
Some scholars like to believe that Ottoman Sunni orthodoxy drew its form by virtue of the Ottoman conquest of Syria and Egypt in 1516-1517. Accordingly, early Ottoman understanding of heterodox Islam was replaced with a more orthodox one as core Islamic lands started to exert their influence on the Ottoman peripheries. Many recent academicians counter this traditional argument by suggesting that the role of Arab ulema in the formation of Ottoman Sunnism is quite negligible or highly limited at best. Others interpret establishment of the Safavid Empire in the sixteenth century as main motivation for Ottoman concentration of Sunni Islam in opposition to Shi’i Iran. Despite such disputes on the origin of this “confessionalization”, they are mainly in agreement that the Ottomans more and more enforced the boundaries of Sunni faith and practice within the empire especially beginning sometime in the second half of the sixteenth century. Political administrative and local studies shall confidently shed new lights on Ottoman experiences of Sunni orthodoxy. In this view, Ottoman Syria, which is situated in the middle of all these discussions, allows us to conduct a field study in the context of Sunni-Shi’i polarization during the time under scrutiny. This paper is going to be one of the first empirical articles, which exclusively focuses on Fakhreddin Maanoğlu and Ali Canpolad i.e., one Shi’i and one Sunni officer of the Ottoman Empire. Our departure point in this paper is to reveal to what extent “sunnitization” of Ottoman Empire played an important role in decision-making of the Ottoman administration between 1570s and 1630s. In a sense, this study aimed to test the real impact of sectarian polarization in the empire by comparing two contemporary Ottoman statesmen who belonged to Shia and Sunni sects of Islam as they governed their provinces in Syria. This kind of comparative studies of the Ottoman governors in terms of their distinct sect has been either not fully taken into consideration or totally ignored before. In the meantime, we shall also shortly explore how the Ottoman formidable enemies of the time interpreted the religious sectarianism and identity politics for the sake of their own security and interests.